Histochemical Studies on the Testis of Adult Ram - GopiKrishna, B.; Raju, N. K.B; Ramayya, P. Jagapathi; Lakshmi, N. Dhana; Dhyana, R. (Indian Journal of Veterinary Anatomy, 2018)
In the present study the basement membrane of the seminiferous tubules, spermatids and capsule showed strong positive reaction for neutral and acid mucopolysaccaharides. Strong reaction for lipids was also noticed in spermatogonia and the primary spermatocytes and moderate reaction in spermatids and Leydig cells. The spermatogonia, primary and secondary spermatocytes and Sertoli cells showed weak reaction for PAS, whereas blood vessels showed moderate reaction for PAS. The Leydig cells showed strong reaction for glycogen. The acid phosphatase activity was strong in the basement membrane and spermatogenic cells and moderate to weak in Leydig cells. Alkaline phosphatase activity was mild in seminiferous tubules and almost negative in the interstitial tissue.